Relatedness and regional specialization in green, digital, and twin economic activities: evidence from the UK - Gloria Cicerone; Sebastian Losacker; Raquel Ortega-Argilés (The Annals of Regional Science, 2026)
This paper examines the geography and relatedness of green, digital, and twin (both green and digital) economic activities across UK local authorities, contributing to debates on whether the two domains are truly synergistic. Using an innovative web-based real-time industry classification dataset covering about 200,000 firms, we identify regional specializations and compute industry-relatedness from firm-level co-occurrence patterns. Spatial mapping and urban scaling analyses reveal interesting patterns: digital industries tend to concentrate in large urban centres, while green and twin industries are more dispersed. Furthermore, regression models show that relatedness in one domain (e.g. green) is positively associated with specialization in the other (e.g. digital), with twin industries exerting the strongest mutual influence on both green and digital domains. These results provide empirical support that capabilities in one domain can facilitate diversification into the other, and that twin activities act as a bridge linking them. By explicitly identifying activities that are simultaneously green and digital, and by quantifying their relatedness to other industries, this paper offers new insights into the structural interdependencies underpinning the twin transition and its geography.
Keywords: O30; O32; Q55; R11; 500